Social and educational impact of euro-orphanhood (based on the research conducted among primary school students) - Matyjas, Bożena (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Euro-orphanhood has become an important social issue which affects thousands of Polish families. The problem of euro-orphanhood has been intensifying since 2004, when Poland joined the European Union. That is when economic migration of parents who left their homes in order to work abroad began. A lot of Polish fathers or mothers, and often both parents, decided to develop their careers abroad. As a result, significant social and educational implications for children left with one parent, grandparents or other family members occurred. In its theoretical part the article examines the concept of euro-orphanhood and describes its nature and range in Poland. It also considers the causes of euro-orphanhood and its effects on children. The empirical part discusses the research findings concerning the social and educational impact of parental economic migration on children. The research, based on diagnostic survey, tracked primary school students, 4th–6th class, from the Świętokrzyskie region. The research thoroughly examined the respondents’ living conditions, family situation (e.g. relationships with parents working abroad, parental support, children’s views of parental absence) as well as their school performance (e.g. school achievements, behavioural issues etc.). Finally, the study considers practical and theoretical conclusions and recommendations.
Keywords: euro-orphanhood; economic migration; children; education; upbringing